How "Paternalistic" Is Spatial Perception? Why Wearing a Heavy Backpack Doesn't—and Couldn't—Make Hills Look Steeper. (July 2013) - Firestone, Chaz
A chief goal of perception is to help us navigate our environment. According to a rich and ambitious theory of spatial perception, the visual system achieves this goal not by aiming to accurately depict the external world, but instead by actively distorting the environment's perceived spatial layout to bias action selection toward favorable outcomes. Scores of experimental results have supported this view—including, famously, a report that wearing a heavy backpack makes hills look steeper. This perspective portrays the visual system as unapologetically paternalistic : Backpacks make hills harder to climb, so vision steepens them to discourage ascent. The "paternalistic" theory of spatial perception has, understandably, attracted controversy; if true, it would radically revise our understanding of how and why we see. Here, this view is subjected to a kind and degree of scrutiny it has yet to face. After characterizing and motivating the case for paternalistic vision, I expose several unexplored defects in its theoretical framework, arguing that extant accounts of how and why spatial perception is ability-sensitive are deeply problematic and that perceptual phenomenology belies the view's claims. The paternalistic account of spatial perception not only isn't true—it couldn't be true, even if its empirical findings were accepted at face value.